2004
DOI: 10.1556/avet.52.2004.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin alters myostatin gene expression in C2C12 muscle cells

Abstract: The objective of the present study was to determine the effects of follistatin addition on myostatin and follistatin gene expression patterns in C 2 C 12 muscle cells. C 2 C 12 cells were administered with 100 ng/ml recombinant human (rh) follistatin in Dulbecco's modified Eagle medium (DMEM) containing 10% fetal bovine serum (FBS), 4 mM glutamine and antibiotics daily for three days. Rh follistatin was not added in the control wells. Follistatin and myostatin gene cDNAs were synthesised by reverse transcripta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…On the other hand, during the stage of complete regeneration, an absence of the myostatin and follistatin proteins and a marked decrease in the expression of both genes were observed 9 weeks after birth in both mouse strains. Interestingly, the myostatin mRNA level significantly increases in C2C12 cells treated with rh-follistatin at an early stage, but then sharply decreases at a late stage (Kocamis et al, 2004). This suggests that the beneficial effect of follistatin would occur in the presence of degenerative and necrotic muscle fibers.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, during the stage of complete regeneration, an absence of the myostatin and follistatin proteins and a marked decrease in the expression of both genes were observed 9 weeks after birth in both mouse strains. Interestingly, the myostatin mRNA level significantly increases in C2C12 cells treated with rh-follistatin at an early stage, but then sharply decreases at a late stage (Kocamis et al, 2004). This suggests that the beneficial effect of follistatin would occur in the presence of degenerative and necrotic muscle fibers.…”
Section: Discussionmentioning
confidence: 94%
“…An antifibrotic process was simultaneously elicited, as evidenced by the stimulation of the expression of a) the myostatin activity inhibitor, follistatin (Hill et al 2002, Amthor et al 2004, Kocamis et al 2004, b) a Smad signaling inhibitor, Smad7 (Forbes et al 2006), and c) a collagen breakdown inducer, matrix metalloproteinase 8 (MMP-8;Siller-Lopez et al 2004). Follistatin did block the upregulation of TGF-b1 expression by myostatin, as shRNA against myostatin (Magee et al 2006) inhibited the expression of PAI-1, which in turn was stimulated autocrinely by the forced over-expression of myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TGF-b1 and activin A, myostatin is inhibited by follistatin, and also by the agents that induce follistatin expression, such as deacetylase inhibitors that block myostatin negative action on the muscle (Lee & McPherron 2001, Amthor et al 2004, Iezzi et al 2004, Kocamis et al 2004. However, it is not known whether myostatin's putative profibrotic action is exerted via the stimulation of myofibroblasts differentiation from their progenitor, or by inducing a switch of the differentiated cell to the synthetic phenotype producing extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Based these findings, we carried out in vivo follistatin administration during the neonatal period in an attempt to neutralize myostatin activity. Kocamis et al [45] showed that myostatin gene expression in C2C12 cells was acutely increased by the addition of recombinant human follistatin, indicating the possibility that follistatin modulates myostatin gene expression in skeletal muscle. However, the results obtained in the present experiment revealed that both myostatin gene expression in skeletal muscle and the protein level in serum were not altered by follistatin when adm i nistra t e d i n v iv o, in d ic at i n g t h a t th e hypertrophic effect of follistatin on skeletal muscle fiber was not due to alteration of myostatin expression.…”
Section: Discussionmentioning
confidence: 99%